A swelling-suppressed Si/SiOx nanosphere lithium storage material fabricated by graphene envelopment. Issue 51 (6th June 2016) - Yoo, Hyundong; Park, Eunjun; Kim, Hyekyoung; Bae, Juhye; Chang, Hankwon; Jang, Hee Dong; Kim, Hansu
Abstract : A swelling-suppressed, Si nanocrystals-embedded SiO x nanospheres lithium storage material was prepared by graphene envelopment. Abstract : A swelling-suppressed, Si nanocrystals-embedded SiO x nanospheres lithium storage material was prepared by graphene envelopment. The free void spaces formed between the graphene envelope and Si/SiO x nanospheres effectively accommodated the volume changes of Si/SiO x nanospheres during cycling, which significantly suppresses the swelling behavior and improves the capacity retention up to 200 cycles.